Bebida hidratante aciborojito - Iza Shulca, Gloria Ximena (2016)
This project aimed to develop a moisturizer-based drink jicama (yacón) and borojó (Borojoa sorbilis). To design the formulation of various combinations of beverage flavoring acidulants and was performed, jicama partial balances and borojó was performed in order to obtain a final product that contains all the necessary nutrients according to INEN standard drinks. Once determined the formulations six samples of the beverage was performed to determine the best treatment all samples contained 60% jicama and 40% borojó which differs are acidulants (tartaric acid, citric acid, ascorbic acid) and natural flavoring (mint, lemon balm). In addition the mixture it added sodium, sucrose chloride as established, then the sample was subjected to a previous pasteurization 60 ° C for a period of 30 minutes for subsequent packaging in polyethylene containers and was kept under refrigeration. Tastings of samples was performed with the help of students of the Center for Physical Culture the Technical University of Cotopaxi, good results are obtained and the best treatment t6 (a3b2) corresponding to the jicama formulation and borojó with citric acid was determined and mint.